The Costs of Austerity: Labor Emigration and the Rise of Radical Right Politics in Central and Eastern Europe - Finnsdottir, Maria Sigridur (Frontiers in Sociology, 2019)
The right to free movement, to move and work freely within the European Union, is a cornerstone right held by EU and EFTA citizens. Labour flows across the EU are, however, not uniform, but are characterized by significant geographic disparities. In particular, since the 2008 global financial crisis, labour emigration, measured by the rate of EU citizens living and working in other EU countries, has increased exclusively among certain Central and Eastern European nations. This paper seeks to examine the link between labour migration, austerity policies, and the rise of radical nationalist politics. This paper uses Boolean analysis to examine the relationships between labour migration, nationalism, welfare support, and austerity. I argue that austerity measures have pushed certain Central and Eastern European countries into the roles of labour sending nations, so that emigration and scarcity put pressure on traditional conceptions of belonging, fueling radical politics. In this way, austerity provides the material and ideological conditions under which emigration comes to be seen as a threat to the wellbeing of the nation, stoking support for nationalist populist parties.